In Situ Quantification of Glucose Concentration in Airway Surface Liquid With Functionalized ZnO Nanorod-Coated Microelectrodes - Pezzulo, Alejandro A. (2011)
The surface of the airways that conduct gases into and out of the lungs has components that protect the host from inhaled and aspirated pathogens. The thin (4–7 µm height) layer of airway surface liquid (ASL) that lines the airways has physicochemical properties that are important for normal function of these antimicrobial components. Among these properties, low glucose concentration is required for normal antimicrobial activity. Current methods for assessing the ASL have important flaws (temporal resolution, dilution factors, collection volume), which have been a recurring obstacle for understanding diseases in which ASL composition is abnormal. To circumvent these problems, microelectrodes coated with ZnO nanorods and immobilized glucose oxidase was used to determine glucose concentration in ASL of well-differentiated cultures of human airway epithelia. The sensor responded to glucose linearly over a concentration range of 0.128 to 8 mM and the effects of electroactive interferents were minimal. The measured concentration of glucose in ASL was consistent with values previously reported. This method confirms the presence of a transepithelial glucose concentration gradient in human airway epithelia and is an important step towards characterizing the physicochemical properties of ASL and understanding diseases caused by changes in ASL composition.